Gauge-including projector augmented-wave NMR chemical shift calculations with DFT+U - Shih, B; Yates, J (American Physical Society, 2017)
We adapt the DFT+U method in the gauge-including projector augmented-wave NMR chemical shift calculations within the plane wave pseudopotential implementation. The nonlocal Hubbard correction potential has been reexamined in order to comply with the gauge-including projector augmented-wave transformation under an external uniform magnetic field. The resulting expression is suitable for chemical shift calculations using both norm-conserving and ultrasoft pseudopotentials in the proector augmented-wave scheme. The implementation is applied to the O17 solid-state NMR chemical shift calculations for transition-metal and rare-earth oxides, including TiO2, ZnO, Ti2O3, La2O3, and CeO2. A comparison between the DFT and DFT+U NMR chemical shifts for the selected materials is presented.